2016
DOI: 10.1016/j.lwt.2016.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure carbon dioxide processing on pectin methylesterase activity and other orange juice properties

Abstract: 6Inactivation of pectinmethylesterase (PME) and quality parameters of orange juice have been 7 studied after high pressure carbon dioxide (HPCD) treatment. The HPCD treatment conditions 8 covered a wide range of temperature from 2 to 40 ºC, far below normal thermal treatment, while 9 operating pressure was varied from 10 to 30 MPa and exposure time from 3 to 60 min. A 10 decrease in PME activity was found, even at the lowest temperature studied in this work, 2 ºC. 11Different inactivation kinetic models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
0
36
0
2
Order By: Relevance
“…Typically, operating pressure does not exceed 50 MPa and temperature ranges between 20 and 50 ºC (Briongos et al, 2016), being lower than the temperature employed in this work in TS. Figure 7 compares the PPO inactivation kinetics by TS at 44 ºC, temperature of the plateau, (V=80 mL and 100 % of amplitude) in the presence of air and by displacing the air with nitrogen, with results obtained in a previous study on inactivation kinetic of PPO from apple juice at 45ºC by HPCD at 20 MPa (Illera et al, 2018).…”
Section: Comparison With Hpcdmentioning
confidence: 98%
See 2 more Smart Citations
“…Typically, operating pressure does not exceed 50 MPa and temperature ranges between 20 and 50 ºC (Briongos et al, 2016), being lower than the temperature employed in this work in TS. Figure 7 compares the PPO inactivation kinetics by TS at 44 ºC, temperature of the plateau, (V=80 mL and 100 % of amplitude) in the presence of air and by displacing the air with nitrogen, with results obtained in a previous study on inactivation kinetic of PPO from apple juice at 45ºC by HPCD at 20 MPa (Illera et al, 2018).…”
Section: Comparison With Hpcdmentioning
confidence: 98%
“…50 mL of pectin solution were mixed with 1 mL of cloudy apple juice and pH was adjusted to 7.5 with NaOH 0.005 N. During pectin hydrolysis at 30 ºC, pH was maintained at 7.5 by adding NaOH 0.005 N. The amount of NaOH added for 15 min was recorded. One PME activity unit (UPE) is defined as the micromoles of carboxylic groups produced per minute and mL of juice, at pH 7.5 and 30 ºC (Briongos et al, 2016).…”
Section: Determination Of Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in viscosity after HPCD treatment might also be related to the decrease of particle size. Effect of HPCD on particle size distribution has been reported in previous publications (Briongos et al, 2016;Illera et al, 2018). It demonstrated that HPCD led to homogenization effect causing smaller particles of juice colloid.…”
Section: Apparent Viscositymentioning
confidence: 67%
“…Most of the published studies were performed on the effects of HPCD on juices with small consistency such as those from orange (Briongos et al, 2016), apple (Liao, Zhang, Hu, & Liao, 2010), carrot (Zhu, Wang, Ramaswamy, & Yu, 2017), mulberry (Zou et al, 2016), coconut (Cappelletti et al, 2015), and watermelon (Liu, Hu, Zhao, & Song, 2012). However, there were fewer papers published on the HPCD potentials for pasteurization of a relatively consistent and viscous pulp.…”
Section: Practical Applicationsmentioning
confidence: 99%